(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
In this research work, the effect of various construction parameters and structural characteristics of weft knitted spacer fabric on the compressive behavior and energy absorption capability was studied. The potential compression mechanism of the fabric was identified with support of the compression stress-strain curve, work done and efficiency at different compression stages. The results show that the compressive stress at the same compressive strain increases with the fabric density, and the stress-strain curves of spacer fabrics with different densities were all composed of initial, elastic region, plateau region and densification region. Third order polynomial regression model was used to establish the elastic deformation properties to obtain the compression results. The spacer fabrics ideal energy-absorption efficiency curves were obtained from their stress-strain curves and all findings show that stress corresponding to at the peak of the energy-absorption efficiency was closed to the densification stress of material. Advance statistical evaluation and one-way analysis of variance is used to analyze the significance of various factors such as thickness, spacer yarn diameter and surface structures on energy absorption at maximum compression load and deformation. These findings are important requirements for designing weft knitted spacer fabrics for cushioning applications in car seats, mattress, shoe insoles etc.